Comparative Proteome Analysis of Wheat Flag Leaves and Developing Grains Under Water Deficit - Deng, Xiong; Liu, Yue; Xu, Xuexin; Liu, Dongmiao; Zhu, Genrui; Yan, Xing; Wang, Zhimin; Yan, Yueming (Frontiers in Plant Science, 2018)
In this study, we performed the first comparative proteomic analysis of wheat flag leaves and developing grains in response to drought stress. Drought stress caused a significant decrease in several important physiological and biochemical parameters and grain yield traits, particularly those related to photosynthesis and starch biosynthesis. In contrast, some key indicators related to drought stress were significantly increased, including malondialdehyde, soluble sugar, proline, glycine betaine, abscisic acid content, and peroxidase activity. Two-dimensional difference gel electrophoresis (2D-DIGE) identified 87 and 132 differentially accumulated protein (DAP) spots representing 66 and 105 unique proteins following exposure to drought stress in flag leaves and developing grains, respectively. The proteomes of the two organs varied markedly, and most DAPS were related to the oxidative stress response, photosynthesis and energy metabolism, and starch biosynthesis. In particular, DAPs in flag leaves mainly participated in photosynthesis while those in developing grains were primarily involved in carbon metabolism and the drought stress response. Western blotting and quantitative real-time polymerase chain reaction (qRT-PCR) further validated some key DAPs such as rubisco large subunit (RBSCL), ADP glucose pyrophosphorylase (AGPase), chaperonin 60 subunit alpha (CPN-60 alpha) and oxalate oxidase 2 (OxO 2). The potential functions of the identified DAPs revealed that a complex network synergistically regulates drought resistance during grain development. Our results from proteome perspective provide new insight into the molecular regulatory mechanisms used by different wheat organs to respond to drought stress.